Characterization of microplastics in sardines (Sardinella lemuru) from Iloilo, Philippines. - Aguilos, Nicole Andrea S.
Sardines play an important role in the country's economic development and ecological well-being. However, the presence of microplastics can threaten marine life, including several commercially important sardines species, and consequently endanger the health and safety of the local consumers. The presence of these microplastics have been reported in several aquatic organisms in recent studies, but reports on its presence and the chemical composition or the polymer types of the reported microplastics, particularly in sardines, are very limited despite the importance of this fishery. In this study, sardines (Sardinella lemuru) from Estancia and Miagao, both in the province of Iloilo, Philippines, were investigated to assess the presence of microplastics and analyze the physical and chemical characteristics of the isolated polymers. Using Rose Bengal staining and stereomicroscopic analyses, results revealed that the meats of sardines from Estancia, Iloilo contain 11 microplastic pieces per 250 grams of meat samples or an average of 1.10 1.28 microplastic pieces per 250 grams of meat samples, while their viscera contained 13 microplastic pieces per 125 grams of visceral samples or an average of 1.30 1.06 MS pieces per 125 grams of visceral sample. Sardines from Miagao showed lower microplastic occurrence than the samples from Estancia, with an estimated 4 microplastic pieces per 250 grams of meat samples or an average of 0.40 0.70 MS pieces per 250 grams of meat sample in the meat and 3 microplastic pieces per 25 grams samples or an average of 0.30 0,48 microplastic pieces per 125 grams of visceral sample in the viscera. Microplastics isolated from the Estancia samples were mostly fragments (66.67%) and fibers (29,17%), with sizes ranging from 3m to 19m, The same polymer forms, i.e., fibers (57.14%) and fragments (28.57%), dominated the samples from Miagao, with sizes ranging from 4m to 25m, Fourier Transformed Infrared - attenuated total reflectance (FTIR-ATR) spectroscopic analysis revealed that the detected microplastics were mostly polyethylene (PE), polypropylene (PP), polyester: terephthalate (PET), and polyvinylchloride (PVC), with PE, PET, and PVC mainly observed in the isolated microplastics from Estancia, while PP dominated the detected microplastics from the Miagao sardines.